2002
DOI: 10.1063/1.1433910
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy in detectivity of GaN Schottky ultraviolet detectors: Comparing lateral and vertical geometry

Abstract: Vertical and lateral geometry GaN-based Schottky barrier photodetectors have been implemented, using similar quality material and the same fabrication process. The vertical detector exhibits two orders of magnitude higher responsivity. This is attributed to improved ohmic backcontacts, due to the highly doped buried layer. The vertical detectors exhibits also lower 1/f noise level, which is attributed to the reduced effect of dislocations on the carrier transport, resulting in lower mobility fluctuations. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 16 publications
(10 reference statements)
0
23
0
Order By: Relevance
“…Using this mesa structure, Lu et al 13 found that the a-particle pulse height spectra have one distinct peak that can be fitted precisely by a Gaussian. Compared with lateral devices, i.e., the double-Schottky contact structure, mesa geometry detectors exhibit superior performance, e.g., a lower noise level and fewer dislocation mobility fluctuations, 87 which are related to the better transport properties of carriers flowing vertically. For these two mesa structures, mesa-1 may suffer from an over-etching problem, since the applied buffer layer is usually thin (less than 2 lm), while mesa-2 needs a high temperature annealing process to form the Ohmic contact.…”
Section: Mesa Structurementioning
confidence: 99%
“…Using this mesa structure, Lu et al 13 found that the a-particle pulse height spectra have one distinct peak that can be fitted precisely by a Gaussian. Compared with lateral devices, i.e., the double-Schottky contact structure, mesa geometry detectors exhibit superior performance, e.g., a lower noise level and fewer dislocation mobility fluctuations, 87 which are related to the better transport properties of carriers flowing vertically. For these two mesa structures, mesa-1 may suffer from an over-etching problem, since the applied buffer layer is usually thin (less than 2 lm), while mesa-2 needs a high temperature annealing process to form the Ohmic contact.…”
Section: Mesa Structurementioning
confidence: 99%
“…Due to autodoping in GaN, it is expected that the barrier region will be n-doped to $10 17 cm À3 even though no intentional doping was carried out. This autodoping may enhance the UV detection by increasing the gain in the UV detector due to trapping of minority carriers at the interface [17]. The bandgap between the valence and conduction bands in Al 0.1 Ga 0.9 N is E G = 6.13x + 3.42(1 À x) À 1.08x(1 À x) eV [18], where x is the Al fraction in the AlGaN barrier.…”
Section: Resultsmentioning
confidence: 99%
“…This material is also remarkably tolerant to aggressive environments, due to its thermal stability and radiation hardness. To date, several groups have reported encouraging results for nitride-based photodetectors, such as p-n junction diode [1,2], p-i-n detectors [3][4][5][6], p-p-n diode [7], Schottky barrier detectors [8][9][10] and metal-semiconductor-metal (MSM) detectors [11][12][13][14][15][16][17][18][19]. Among these structures, Schottky-barrier detectors are an attractive choice for UV detectors, given their fabrication simplicity and much faster response speed.…”
Section: Introductionmentioning
confidence: 99%